From a Ladder to a mere Rung: The Functions of the Phenomenology of Spirit within or without the Encyclopedia - Chaput, Emmanuel (Revista Eletrônica Estudos Hegelianos, 2021)
In this paper, I explore the distinct functions that Hegel assigns to the Jena Phenomenology of Spirit (1807) and to the Encyclopedia’s ‘Phenomenology of Spirit’. Whereas the 1807 Phenomenology can be seen as a ladder bringing natural consciousness up to the level of philosophical knowledge, the Encyclopedia Phenomenology seems demoted to a mere rung, a mere step or a subsection within Hegel’s definitive system, stuck between the sections on Anthropology and Psychology. Does that entail that what was once (in 1807) conceived as the first part of Hegel’s system of science has become secondary in importance in regards to the Logic which constitutes the first part of Hegel’s Encyclopedia? I argue against such a view that it is important to distinguish the Jena Phenomenology from the Encyclopedia’s, in order to understand how they both serve different purposes which remained to the end of the highest importance in regards to the general economy of Hegel’s final system. This in turn implies that we have two distinct ‘phenomenological’ moments within Hegel’s system that need to be appraised in their own right.